Elements of game design - Zubek, Robert, ....- (Cambridge (Mass.) : The MIT Press, 2020)
"Elements of Game Design" is an introductory text on game design. The goal is to teach students a structured process of design applicable to games and interactive experiences, and introduce the vocabulary and techniques of practicing game designers. The text draws on the author's experience as a professional game developer, as well as a teacher of an intro-level game development class. The book begins by introducing the user-centered design paradigm, and explain a games-specific process that splits the design problem into several conceptual stages. The bulk of the text explores those stages in detail, and teaches how to analyze and resolve them. Throughout the text we introduce the technical vocabulary and concepts used by designers in the industry, and illustrate the particular lessons with numerous real-life examples. The text ends with a review of the overall process and its application in the production of new games"--
Elements -- Player experience -- Mechanics -- Systems -- Gameplay -- Macrostructure -- Prototyping and playtesting.
Includes bibliographical references and index.
Keywords: Computer games -- Design; Games -- Design and construction; Video games -- Design